Digital identification and adulteration analysis of Codonopsis Radix and Stellariae Radix based on the “digital identity” of chemical compositions - Wang, Xianrui; Zhang, Jiating; Jing, Wenguang; Guo, Xiaohan; Li, Minghua; Cheng, Xianlong; Wei, Feng (Frontiers in Chemistry, 2024)
Under the background of digitalization of traditional Chinese medicine (TCM), to realize the digital identification and adulteration analysis of Codonopsis Radix (CR) and Stellariae Radix (SR) based on the chemical analysis. This study combined digitalization concepts and chemical analysis and conducted chemical analysis on CR and SR from different batches based on UHPLC-QTOF-MS E .Further, the shared ions were extracted from different batches of CR and SR as their "ions characterization" respectively after digital quantization. Then, the data matrices of unique ions of CR relative to SR and SR relative to CR were screened out, and the Top-N ions were outputted as the "digital identities" of CR and SR, sorted by ionic strength. Finally, the above "digital identities" of CR and SR were used as benchmarks for matching positive samples and market samples to give feedback on the matching credibility (MC) for identification and adulteration analysis. The results showed that based on the "digital identities" of CR and SR, the digital identification of CR, SR, and positive samples can be realized at the individual level of TCM efficiently and accurately, even if 3 % of SR in the mixed samples can still be identified efficiently and accurately. Moreover, one of the 12 batches of market samples was identified as an adulterated sample. It proved that the identification and adulteration analysis of two herbs can be realized efficiently and quickly through the "digital identities" of chemical compositions. It has important reference significance for developing digital identification of CR and SR at the individual level of Chinese medicine based on the "digital identity" of chemical compositions, which was beneficial to the construction of digital quality control of CR and SR.